APOL1 risk genotype in European steroid-resistant nephrotic syndrome and/or focal segmental glomerulosclerosis patients of different African ancestries. Issue 11 (9th July 2018) - Gribouval, Olivier; Boyer, Olivia; Knebelmann, Bertrand; Karras, Alexandre; Dantal, Jacques; Fourrage, Cécile; Alibeu, Olivier; Hogan, Julien; Dossier, Claire; Tête, Marie Josèphe; Antignac, Corinne; Servais, Aude
Abstract: Background: Apolipoprotein L1 ( APOL1 ) risk variants are strongly associated with sporadic focal segmental glomerulosclerosis (FSGS) in populations with African ancestry. We determined the frequency of G1/G2 variants in steroid-resistant nephrotic syndrome (SRNS)/FSGS patients with African or French West Indies ancestry in France and its relationships with other SRNS genes. Methods: In a cohort of 152 patients (139 families), the APOL1 risk variants were genotyped by direct Sanger sequencing and pathogenic mutations were screened by next-generation sequencing with a panel including 35 SRNS genes. Results: The two risk allele [high-risk (HR)] genotypes were found in 43.1% (66/152) of subjects compared with 18.9% (106/562) in a control population (P < 0.0001): 33 patients homozygous for APOL1 G1 alleles, 4 homozygous for G2 and 29 compound heterozygous for G1 and G2. Compared with patients in the low-risk (LR) group, patients in the HR group were more likely to originate from the French West Indies than from Africa [45/66 (68.2%) versus 30/86 (34.9%); P < 0.0001]. There were more familial cases in the HR group [27 (41.5%) versus 8 (11.4%); P < 0.0001]. However, causative mutations in monogenic SRNS genes were found in only 1 patient in the HR group compared with 16 patients (14 families) in the LR group (P = 0.0006). At diagnosis, patients in the HR group without other mutations were more often adults [35 (53.8%) versus 19 (27.1%); P = 0.003] and had a lower estimated glomerular filtration rate (78.9 versus 98.8 mL/min/1.73 m 2 ; P = 0.02). Conclusions: The HR genotype is frequent in FSGS patients with African ancestry in our cohort, especially in those originating from the West Indies, and confer a poor renal prognosis. It is usually not associated with other causative mutations in monogenic SRNS genes.